WAJAH ISLAM PRIODE MAKKAH-MADINAH DAN KHULAFAURRASYIDIN - Mohammad Adnan (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2019)
Talking about Islam that exists today is a continuation of Islam which has become history in the past. This means that when we try to uncover the essence of the meaning that exists in Islam today, of course we must look at how Islam in the past (reading history). In this context when we talk about Islamic history we certainly will never be separated from the early history of the emergence of Islam itself. Knowledge of history is very important because it will add insight and understanding of a past situation and provide a comparison of a situation that was formerly with the current situation. In the context of religion, for example, the religion of the Arabs before Islam did inherit Abraham and Ismail's religion as a tawheed religion, but with such a long distance between Prophet Ibrahim and the Prophet Muhammad had made it possible for the Arabs to turn away from belief in monotheism in polytheistic and paganism beliefs . With the arrival of Islam the belief in monotheism became the most fascinating beginning of the world. It does not stop there, Islam continues to develop in political and economic matters, especially in the government of the Khulafaurrasyidin. But the foundation of all that was built by the Prophet Muhammad during the time of Makkah-Madinah and was developed during the Khulafaurrasyidin.